Four new species of the genus Mannerheimia Mäklin, 1880 (Coleoptera: Staphylinidae: Omaliinae) from south-western China and Taiwan - Shavrin, Alexey V. (Zootaxa, 2018)
Four new species of the genus Mannerheimia Mäklin, 1880 from south-western China and Taiwan are described and illustrated: M. grandilobata Shavrin, sp.n. (China: Yunnan), M. emeishanensis Shavrin, sp.n. (China: Sichuan), M. maculata Shavrin, sp.n. (China: Yunnan) and M. taiwanica Shavrin, sp.n. (Taiwan: Taichung Hsien, Nantou Hsien), the first records of the genus from China and Taiwan. A key to species known from China and Taiwan and distributional maps for each species are provided.